(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
recent development of self assembled supramolecular chemistry can rationally design and synthesize metalorganic coordination polymers depending on the ligand geometry and coordination propensity of the metal ion. Organic ligand formed by reaction between the amino acids and aldehydes are good candidates to construct metal clusters more and more geometrically intriguing. Supramolecular structures derived from such ligands, for example, helices5, capsules6 and polymer clusters with different number of metal ions7, 8 have successfully obtained. Semicarbazone and thiosemicarbazone ligands are commonly used as ligands in coordination chemistry and are biologically active compounds. Their complexation with different metals enhances the biocidal activity of these molecules. These metal based complexes have attracted considerable interest in chemical and biological studies due to their potentially beneficial biological activity which may be attributed to formation of them chelates with metal ions.